2013
DOI: 10.1371/journal.pone.0060925
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Growth of Open Access in the Biomedical Field: Analysis of PubMed Articles from 2006 to 2010

Abstract: IntroductionThis study clarifies the trends observed in open access (OA) in the biomedical field between 2006 and 2010, and explores the possible explanations for the differences in OA rates revealed in recent surveys.MethodsThe study consists of a main survey and two supplementary surveys. In the main survey, a manual Google search was performed to investigate whether full-text versions of articles from PubMed were freely available. Target samples were articles published in 2005, 2007, and 2009; the searches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 8 publications
(8 reference statements)
1
41
0
4
Order By: Relevance
“…Since the release of the Budapest Open Access Initiative (BOAI) in 2002, numerous efforts have been made by governments, funders, institutions and publishers to promote OA (6,7). In April 2008, the US National Institutes of Health (NIH) began to require that all grantees submit to PubMed Central (PMC) their final manuscripts upon acceptance for publication, to be made OA no later than 12 months after the publication date (8).…”
Section: Introductionmentioning
confidence: 99%
“…Since the release of the Budapest Open Access Initiative (BOAI) in 2002, numerous efforts have been made by governments, funders, institutions and publishers to promote OA (6,7). In April 2008, the US National Institutes of Health (NIH) began to require that all grantees submit to PubMed Central (PMC) their final manuscripts upon acceptance for publication, to be made OA no later than 12 months after the publication date (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that about 50% of biomedical research in general [5] and 60% of RCTs in dentistry [6] are behind the paywall. Healthcare professionals usually rely on abstracts to initially appraise a trial, decide whether or not to retrieve more information, or even directly inform their healthcare decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…This debate has been heightened in the UK, and internationally, by the Finch Report and subsequent RCUK policy development which signalled a preference for Gold. The biomedical discipline has tended to favour gold rather than green to date in any case, 14 although most of the policies reported in this study allow either, permitting no more than a six-month embargo period. It is important to note, however, that OA journal publishing and repository development are not necessarily mutually exclusive OA models (despite the sometimes polarized debate).…”
Section: Discussionmentioning
confidence: 80%
“…Initially, they highlight some of the circumstances which gave rise to the Trust's OA policy including an exercise which showed that only 6% of articles reporting Wellcome-funded research were freely available on the Web. 14 Were the Trust to fund all papers which cite the Wellcome as a funder, Walport and Kiley estimate it would cost around 1.5% of their total research spend, although with the funding of many research projects shared with other funders, this percentage would be expected to fall as others adopt OA policies. As well as funding APCs, they also describe the Wellcome's investment in creating a version of PubMed Central in the UK, a service which in its expanded form, Europe PMC, has now been supported by a number of other funders in the biomedical fi eld.…”
Section: Literature Reviewmentioning
confidence: 99%